Direct Laser Metal Deposition of AISI H13 Cladding on Copper–Beryllium Alloy Substrate Through a Stainless‐Steel Buffer Layer Strategy. Issue 4 (3rd April 2023) - Zhao, Zhao; Perini, Matteo; Bosetti, Paolo; Pellizzari, Massimo
Abstract : In article number 2200387, Zhao Zhao and co‐workers demonstrate that the Scheil solidification model can simply estimate solidification cracking susceptibility when cladding dissimilar alloys. Meanwhile, tool steel/Copper‐beryllium alloy bimetallic structures could have a bright future in molding industries regarding their excellent performance in load‐bearing capability and thermal conductivity simultaneously.